Case Study: Application of Evidence-Based Nursing Warm Compresses to Reduce Pain Levels in Children with Lymphadenopathy in the Wijaya Kusuma Ward at Kardinah Regional General Hospital, Tegal City - Ratna Kuning Budi Rahayu, Atik; Purbasari, Dwiyanti; Karlina, Nonok (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Lymphadenopathy is the enlargement of lymph nodes or a condition in which lymph nodes become enlarged to a size greater than 1 cm and the epicondylar lymph nodes are palpable with a size greater than 5 mm, which is an abnormal condition. Method: This study employed a qualitative approach using a case study design with a nursing perspective. Result: The case study results indicated that warm compresses were effective in reducing acute pain in An. N.S.A. with lymphadenopathy. Conclusion: After receiving nursing care for 4 days, the evaluation results for the initial diagnosis were supported by the client's subjective data stating that the pain was no longer felt, reinforced by objective data showing a body temperature of 36.5°C, a pulse rate of 95 beats per minute, a respiration rate of 20 breaths per minute, and no further pain reported on the pain scale. The assessment results indicated that the issue was resolved, and the intervention plan was discontinued as the intervention had been implemented for 4 days. In the second diagnostic evaluation, the subjective findings indicated that the client's family reported that the child had finished their meal portion. This was supported by objective data showing that the patient did not appear pale and had finished their meal portion. The assessment concluded that the issue had been resolved, and the intervention plan was discontinued as the necessary actions had been implemented over the 4-day period.